Prevalence of Depression, Anxiety, and Stress Among Repatriated Indonesian Migrant Workers During the COVID-19 Pandemic - Harjana, Ngakan Putu Anom; Januraga, Pande Putu; Indrayathi, Putu Ayu; Gesesew, Hailay Abrha; Ward, Paul Russell (Frontiers in Public Health, 2021)
Introduction: Repatriated Indonesian migrant workers are vulnerable to getting serious mental health problems during the COVID-19 pandemic. This study aimed to assess the prevalence and associated factors of depression, anxiety, and stress among these populations during the COVID-19 pandemic. Methods: Guided by the health belief model, a cross-sectional study design was employed among 335 participants, and primary data were collected through an online survey. Measured by using DASS-21, anxiety, depression, and stress were the dependent variables. We performed descriptive and inferential statistical analyses—logistic regression was used to predict independently associated variables. STATA was used to execute all data analyses. Results: The prevalence of depression, anxiety, and stress among repatriated Indonesian migrant workers were 10.15%, 9.25%, and 2.39%, respectively. The risk of anxiety and depression was low among those aged 21-30 years old, completed university degree, married, and quarantined for 14-days. Conversely, the risk of anxiety and depression was high among those who had bad perceived health status, high perceived susceptibility, and negative stigma perception. Conclusion: The prevalence of depression, anxiety, and stress among repatriated Indonesian migrant workers was relatively low compared to the general population. The risk of anxiety and depression was low among youngsters, educated and those under effective quarantine study participants, but the risk was high among those who had negative perceptions about their health, stigma, and susceptibility to the disease.